Laryngeal Aerodynamic Measures in Normal Adults - P, Gopi Kishore; M, Pushpavathi; S, Sheela (Journal of All India Institute of Speech and Hearing, 2020)
Laryngeal aerodynamic analysis measures respiratory and laryngeal functions reflecting the coordinative nature of voice production. The present study primarily aimed at establishing the normative data for four laryngeal aerodynamic parameters viz. Estimated Sub- Glottic Pressure (ESGP), Mean Air Flow Rate (MAFR), Laryngeal Airway Resistance (LAR), and Laryngeal Airway Conductance (LAC) in adult Indian population. A second purpose was to examine the effect of age and gender on these measures. Eighty five participants including 54 males and 31 females in the age range of 18-40 years, with no known problems in voice were considered for the study. Aeroview from Glottal Enterprises was used to record and analyze the data. The participants were instructed to produce CV syllable train “papapapa” into the circumvented mask at comfortable loudness and pitch. Thus recorded stimuli were analyzed to obtain all four parameters (mentioned earlier). Mean and standard deviation for the all the parameters were calculated separately for both the groups of males and females. Box plots were drawn and 8 outliers were removed manually from the main data. Two way MANOVA (performed on remaining data) revealed significant main effects of age for the parameters ESGP and LAC. No significant main effects of gender were observed for the any of the laryngeal aerodynamic parameters studied. The data obtained from this study can be used as normative for laryngeal aerodynamic analysis in the adult population in the age range of 18–40 years.